2014
DOI: 10.1002/chem.201304404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanoporous Carbon–Cobalt‐Oxide Hybrid Electrocatalysts by Thermal Conversion of Metal–Organic Frameworks

Abstract: Nanoporous carbon-cobalt-oxide hybrid materials are prepared by a simple, two-step, thermal conversion of a cobalt-based metal-organic framework (zeolitic imidazolate framework-9, ZIF-9). ZIF-9 is carbonized in an inert atmosphere to form nanoporous carbon-metallic-cobalt materials, followed by the subsequent thermal oxidation in air, yielding nanoporous carbon-cobalt-oxide hybrids. The resulting hybrid materials are evaluated as electrocatalysts for the oxygen-reduction reaction (ORR) and the oxygen-evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
147
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(148 citation statements)
references
References 94 publications
1
147
0
Order By: Relevance
“…In the pursuit of advanced ESSs, more attention should be paid to the correlation between material design and electrochemical performance of the materials. [174][175][176][177][178][179][180] In this respect, the recent progress presented here in the material design of spinel-type transition metal oxides with tunable shapes, porosity, sizes, and compositions will provide practical guidelines for building highly reliable and high performance energy storage materials. …”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In the pursuit of advanced ESSs, more attention should be paid to the correlation between material design and electrochemical performance of the materials. [174][175][176][177][178][179][180] In this respect, the recent progress presented here in the material design of spinel-type transition metal oxides with tunable shapes, porosity, sizes, and compositions will provide practical guidelines for building highly reliable and high performance energy storage materials. …”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Das et al reported a generalized strategy for the synthesis of crystalline metal oxide nanoparticles embedded in a carbon matrix by a controlled thermolysis of MOFs. [23] Yamauchi et al demonstrated that the creation of nanoporous carbon-Co 2 O 3 hybrid materials via a two-step thermal conversion of ZIF-9, [24] while Guangju et al obtained N-doped carbon-Co 3 O 4 composites using a one-step thermal conversion from a specific MOF, Co-I-MOF. [25] Most recently, we utilized a typical sodalite topology ZIF-8, which is built from corner-shared tetrahedral ZnN 4 units and the coordination bonds between the Zn 2+ ions and 2-methylimidazole anions that are amongst the most stable N-donor ligands, [26] to synthesize ZnO/porous carbon composites by the direct carbonization in argon atmosphere, but no XRD peaks related to either ZnO or Zn can be observed in these composites.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are extensive interests in studying some electrochemical reactions, such as oxygen evolution reaction (OER), hydrogen evolution reaction, oxygen reduction reaction (ORR), and carbon monoxide (CO) oxidation, which are core steps in many sustainable energy techniques 1, 2, 3, 4, 5, 6, 7. Besides enthusiastic efforts to search for new electrocatalysts to facilitate these processes, numerous studies are also devoted to making better use of the existing electrocatalysts for achieving optimal properties 2, 8, 9, 10, 11.…”
mentioning
confidence: 99%